The concept of merdeka-belajar-based training management at training institutions - Irma Djanapa Bulow (12 Waiheru, 2025)
Merdeka Belajar (Freedom to Learn) is a government policy that must be adopted by training institutions so that changes are needed in planning, implementation, and post-training evaluation. This study analyzes planning, implementation, and evaluation based on Merdeka belajar. This research method is a literature review, where data is obtained from journals and book references related to Merdeka belajar. The findings show that (1) Merdeka-Belajar-based training planning is oriented towards the needs of training participants identified by training institutions, then categorized into very much needed, reasonably needed, and not required activities. (2) The implementation of Merdeka-belajar-based training can be seen in one of the supervisor leadership training programs, where the main requirement is that participants must prepare change actions. The concept of merdeka-belajar-based training management gives training participants the freedom to be creative and innovative to make office activities effective and efficient. 3) Evaluation of merdeka-belajar-based training can be seen in activities involving stakeholders in preparing training programs, providing opportunities for stakeholders to provide input related to obstacles and problems in participating in training.